HUBUNGAN SELF EFFICACY DENGAN SIKAP DALAM PEMBERIAN AIR SUSU IBU (ASI) EKSLUSIF DI WILAYAH KERJA PUSKESMAS SORIUTU KABUPATEN DOMPU - Sri Hardiani; Haryani; Reni Junari; Fidiya Rizka (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2024)
Abstarct Background: Breastfeed is the first, main, and best food for babies that is natural. Exclusive Breastfeeding has many benefits both for mothers and for babies, the success of breastfeeding can be influenced by Self efficacy and attitude, The problems that arise found by researchers in the working area of the Soriutu Health Center are that there are still 192 babies less than 6 months old who do not get Exclusive Breastfeeding. Purpose: to find out the relationship between self-efficacy and attitude in the provision of exclusive Breastfeeding in the working area of the Soriutu Health Center, Dompu Regency. Method: The research is observational analysis, cross sectional approach, the population in this study is 100 people, the sampling technique used is non probability sampling with total sampling using questionnaire measuring tools, and the analysis used is Univariate and Bivariate analysis, with a spearman rank test. Results: Self efficacy with attitude obtained a significance value of p-value = 0.000 < α = 0.05, from the results of the calculation it can be seen that the relationship between self efficacy and family attitude in providing exclusive breast milk (ASI) with a correlation coefficient number of 0.487. Conclusion: There is a relationship between self-efficacy and attitude in the provision of Exclusive Breastfeeding in the working area of the Soriutu Health Center, Dompu Regency.